Sedative and cardiorespiratory effects of low doses of xylazine with and without acepromazine in Nordestino donkeys - Lucas Castillo, J. A.; Gozalo-Marcilla, M.; Werneck Fonseca, M.; Possebon, F. S.; da Rosa, A. C.; de Araujo Aguiar, A. J. (Wiley, 2018)
Background: Information on appropriate protocols for sedation of Nordestino donkeys is scarce. Objectives: To evaluate the sedative and cardiorespiratory effects of low doses of intravenous (i.v.) xylazine with and without acepromazine in 'Nordestino' donkeys. Study design: Seven healthy female Nordestino donkeys (150 ± 18 kg) were included in this blinded, randomised, crossover experiment. Methods: Four treatments were administered, consisting of two i.v. injections, at baseline (T0, 1st injection) and 15 min later (T15, 2nd injection). Treatments included acepromazine 0.05 mg/kg bwt + saline (AS), saline + xylazine 0.5 mg/kg bwt (SX0.5), acepromazine + xylazine 0.25 mg/kg bwt (AX0.25) or acepromazine + xylazine 0.5 mg/kg bwt (AX0.5). Sedative and cardiorespiratory parameters were evaluated before T0 and 15, 20, 30, 45, 60, 75 and 90 min after treatment. Degree [height of head above ground (HHAG)] and quality of sedation [ataxia, responses to stimuli and visual analogue scale (VAS) scoring] and respiratory rate were evaluated by the main investigator in situ, and heart rate was measured by an assistant investigator. Three experienced evaluators assessed vídeos for ataxia and responses to stimuli. Normal data were analysed by repeated measures ANOVA, and non-normal by Kruskal-Wallis (P<0.05). Results: HHAG was lower than baseline for 15 min after xylazine administration in AX0.25 and for 30 min in SX0.5 and AX0.5 groups. All treatments with xylazine increased VAS and ataxia scores in situ for 15 min after xylazine administration, with no differences between groups. Ataxia scores in situ were higher in SX0.5 and AX0.5 groups than AS for 15 and 30 min after xylazine administration, respectively. Main limitations: Absence of a negative control group (saline-saline). Conclusion: Acepromazine added to xylazine at 0.25 mg/kg bwt produced briefer and milder sedation than xylazine at 0.5 mg/kg bwt.
Keywords: Acepromazine; Cardiorespiratory; Donkeys; Horse; Sedation; Xylazine